Cenas alfabetizadoras - De Conto, Marlí (My University, 2024)
The dissertation is linked to the line of History and Philosophy of Education and the researcher to the Pedagogy of Difference Study Group. The research has as title, and theme, the literacy scenes, its cartographic method focuses on classroom scenes (RANCIÈRE, 2021, LADEIRA, 1978, CORAZZA, 2005) written in the atelier space by literacy teachers from the Municipality of Veranópolis - RS. In this space, the question arises: how do the literacy teachers participating in the atelier teach literacy? The research text is formed by cartographic lines that are made in four blocks: the first shows life scenes of a teacher (CORAZZA, 2005) and classroom scenes that move the cartographer-literacy teacher. The second block moves studies of the literacy pedagogies: the literacy methods, the psychogenetic processes and the literacy (MATOS, 2009; MORTATTI, 2000; 2004; SOARES, 2001). The third block shows the elaboration of the atelier. The last block - closing the study with the scenes written by twelve literacy teachers from the Municipality of Veranópolis - RS - brings back the dissertation question, affirming that the participants from the atelier teach literacy the way the french writer Roland Barthes (2003b) named: how of living together. The scenes written express that the literacy teachers teach literacy through rhythms of hetero-rhythmy and idio-rhythm (BARTHES, 2003b). The literacy scenes through rhythms of hetero-rhythmy are written by the practices of literacy pedagogies. The heterorhythmic scenes themselves also express an attempt at literacy rhythm, searching the movement of idio-rhythm - the movement to remove the most singular moments during the literacy process in the classroom. [resumo fornecido pelo autor]
A dissertação está vinculada à linha da História e Filosofia da Educação e a pesquisadora ao Grupo de Estudos Pedagogia da Diferença. A pesquisa tem como título, e tema, cenas alfabetizadoras, seu método cartográfico foca em cenas (RANCIÈRE, 2021, LADEIRA, 1978, CORAZZA, 2005) de sala de aula escritas no espaço de ateliê pelas alfabetizadoras do Município de Veranópolis - RS. Neste espaço se problematiza: como as alfabetizadoras participantes do ateliê alfabetizam? O texto da pesquisa forma-se por linhas cartográficas que se faz em quatro blocos: o primeiro mostra cenas de vida de uma professora (CORAZZA, 2005) e de sala de aula que movimentam cartógrafa-alfabetizadora. O segundo bloco movimenta os estudos das pedagogias alfabetizadoras: os métodos de alfabetização, processos psicogenéticos e o letramento (MATOS, 2009; MORTATTI, 2000; 2004; SOARES, 2001). No terceiro bloco, apresenta-se a elaboração do ateliê. O último bloco - fechando o estudo, com as cenas escritas por doze alfabetizadoras do Município de Veranópolis - RS -, retoma a pergunta da dissertação, afirmando que as participantes do ateliê alfabetizam do modo como o escritor francês Roland Barthes (2003b) denominou: como viver junto. As cenas escritas expressam que as alfabetizadoras alfabetizam por meio dos ritmos de heterorritmia e de idiorritmia (BARTHES, 2003b). As cenas de alfabetização pelo ritmo de heterorritmia são escritas pelas práticas das pedagogias alfabetizadoras. As próprias cenas de heterorritmia também expressam uma tentativa de ritmo de alfabetização, buscando o movimento da idiorritmia - movimento de retirar o mais singular do que se passa durante o processo de alfabetização na sala de aula. [resumo fornecido pelo autor]
Keywords: Alfabetização; Educação; Professores - Formação; Literacy; Education; Teachers, Training of